Analog and digital circuits for electronic control system applications : using the TI MSP430 microcontroller - Luecke, Gerald (Elsevier/Newnes, 2005)
Todays control system designers face an ever-increasing need for speed and accuracy in their system measurements and computations. New design approaches using microcontrollers and DSP are emerging, and designers must understand these new approaches, the tools available, and how best to apply them. This practical text covers the latest techniques in microcontroller-based control system design, making use of the popular MSP430 microcontroller from Texas Instruments. The book covers all the circuits of the system, including: Sensors and their output signals Design and application of signal conditioning circuits A-to-D and D-to-A circuit design Operation and application of the powerful and popular TI MSP430 microcontroller Data transmission circuits System power control circuitry Written by an experienced microcontroller engineer and textbook author, the book is lavishly illustrated and includes numerous specific circuit design examples, including a fully tested and documented hands-on project using the MSP430 that makes use of the principles described. For students, engineers, technicians, and hobbyists, this practical text provides the answers you need to design modern control systems quickly and easily. * Seasoned Texas Instruments designer provides a ground-up perspective on embedded control systems * Pedagogical style provides a self-learning approach with examples, quizzes and review features * CD-ROM contains source code and more!